Comparison of CABG and PCI in NSTE-ACS patients with three-vessel coronary artery disease. (14th October 2021) - Li, T; Yuan, J
Abstract: Background: Evidence is lacking on the choice between coronary artery bypass graft (CABG) and percutaneous coronary intervention (PCI) in the specific setting of non-ST-segment elevation acute coronary syndrome (NSTE-ACS), especially for complex cases with three-vessel coronary artery disease (TVD). Purpose: To compare PCI and CABG in NSTE-ACS patients with TVD; to explore effects of age and sex on outcomes of different revascularisation strategies. Methods: The present study was a post hoc analysis of data from a single-centre prospective cohort of 8, 943 patients with TVD [(angiographically confirmed stenosis of ≥50% in all three main epicardial coronary arteries (left anterior descending, left circumflex, and right coronary arteries), with or without left main lesion]. Patients were consecutively enrolled from April 2004 to February 2011 to evaluate their prognosis after receiving three different treatments. The study contained 2, 812 patients (PCI, n=1, 559; CABG, n=1, 253) after excluding 1, 489 with ST-segment elevation myocardial infarction, 3, 532 with stable coronary artery disease, and 1, 110 receiving conservative treatment. The patients were divided into three age groups and two sex groups. Subgroup analyses were performed according to presence of diabetes, pre-procedural synergy between percutaneous coronary intervention with taxus and cardiac surgery (SYNTAX) score, and presence of left main lesion. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE), a composite of all-cause death, myocardial infarction and stroke. Results: During a median follow-up of 6.7 years, the risk of MACCE was significantly lower after CABG than after PCI in all patients (HR=0.6764, 95% CI: 0.5528–0.8277), two younger age groups (<65 years: HR=0.6617, 95% CI: 0.4947–0.8852; 65–74 years: HR=0.6997, 95% CI: 0.5124, 0.9556), and male (HR=0.6682, 95% CI: 0.5263–0.8482) (Figure 1). No significant interaction between age and revascularization strategies was observed, neither was it between sex and revascularization strategies. Notably, compared with PCI, CABG was associated with significantly higher risk of MACCE in women ≥75 years of age (HR=3.2716, 95% CI: 1.4213–7.5308, interaction p with sex=0.0007, interaction p with age=0.0024). Effects of age and sex on outcomes of different revascularisation strategies remained neutral regardless of patients' diabetic status, pre-procedural SYNTAX score, and presence of left main lesion (Figure 2). Conclusion: CABG is superior to PCI in terms of MACCE regardless of patients in most NSTE-ACS patients with TVD except women ≥75 years of age. However, we found no significant age- or sex-related difference in prognosis of CABG relative to PCI. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Key Research and Development Program of China